PENGARUH DOSIS PERENDAMAN EKSTRAK DAUN CENGKEH (Syzygium Aromaticum) TERHADAP DAYA TETAS TELUR IKAN LELE DUMBO (Clarias gariepinus) - Baiq Nadia Dwi Yulihastiana; Nunik Cokrowati; Andre Rachmat Scabra (Universitas Mataram, 2021)
This study aims to determine the optimal dose of clove leaf extract immersion on hatchability of catfish eggs and to determine the effect of immersion in clove leaf extract on hatchability of catfish eggs. This research was conducted for 41 days from 17 November 2020 to 27 December 2020, where the research was carried out at the installation of the Kumbung Stone Cultivation Center, Lingsar, West Lombok. This research was conducted with an experimental method using a completely randomized design (CRD) with four treatments and three replications, namely treatment A: control, B: 50 ppm. C: 70 ppm and D: 90 ppm E: 11 ppm. The results showed that the highest hatchability rate of African catfish (Clarias gariepinus) was obtained in treatment D which reached 94.770.17% and the lowest hatchability value in treatment A was 33.33%. ANOVA results showed that there was a significant difference in the effect of soaking the extract. Clove leaves against the hatchability of African catfish eggs in each treatment there was anti-fungal activity, clove leaf extract was at the best dose in the inhibition mechanism against fungi